Hamlet's Blackberry : a practical philosophy for building a good life in the digital age - Powers, William, 1961- (New York : Harper, 2010)
"A soulful polemic that challenges the sacred dogma of the digital age--that the more we connect with others, the happier we are--arguing that as our electronic connectedness grows, we are pulled away from the relationships and experiences that give life texture, depth, and meaning"--
Includes bibliographical references (p. [245]-267).